Comparative Outcomes of Left Anterior Descending, Left Circumflex, and Right Coronary Artery Lesions Treated with Primary Percutaneous Coronary Intervention: A Retrospective Study - Shah, Syed Bilal; Raja Khan, Fahad; Shah, Syed Muzammil; Kamal, Atif; Nazir, Seema; Farooq , Nasir (Indus Journal of Bioscience Research, 2024)
Background: Coronary artery disease is one of the leading causes of morbidity and mortality worldwide. The management of this condition often involves primary percutaneous coronary intervention, which targets specific coronary arteries, including the left anterior descending (LAD), left circumflex (LCX), and right coronary artery (RCA). Differences in outcomes based on the location of these lesions necessitate a thorough understanding of lesion-specific risks to improve patient care and outcomes. Objective: The primary objective of this study was to compare the clinical outcomes of primary percutaneous coronary intervention performed on lesions located in the left anterior descending, left circumflex, and right coronary arteries, with a focus on the incidence of major adverse cardiac events within 30 days post-procedure. Methods: This retrospective cohort study was conducted at Ayub Teaching Hospital, Abbottabad from January 1, 2023, to December 31, 2023. A total of 292 participants (117 with LAD lesions, 88 with LCX lesions, and 87 with RCA lesions) presenting with acute coronary syndrome were treated with primary percutaneous coronary intervention. Based on clinical evaluation, drug-eluting stents or drug-eluting balloons were used. Data were collected from electronic medical records, capturing demographics, comorbidities, procedural details, and outcomes. Statistical analysis, including chi-square tests, independent t-tests, and logistic regression, was performed using SPSS software to identify predictors of major adverse cardiac events. Results: The LAD artery lesions demonstrated the highest incidence of major adverse cardiac events (30.8%) within 30 days, followed by lesions in the LCX artery (20.5%) and RCA artery (17.1%). Mortality was highest in participants with LAD artery lesions (10.3%) compared to LCX (6.8%) and RCA lesions (3.4%). Logistic regression identified age, hypertension, diabetes, and LAD artery lesions as significant predictors of major adverse cardiac events (p < 0.05). Conclusion: This study highlights the significant impact of lesion location on outcomes following primary percutaneous coronary intervention. Lesions in the LAD artery are associated with a higher risk of adverse events, necessitating more intensive monitoring and personalized management. Although RCA lesions generally exhibit better outcomes, careful management is still required when proximal blockages are present. Personalized treatment strategies based on lesion location and individual patient risk factors are essential for optimizing clinical outcomes